(untitled) (Scientific journal of the Fergana State University, 2025)
This article studies the structural-semantic analysis of oxymorons in Abdulla Qahhor’s story “Muhabbat”. Oxymorons enrich the text’s semantic content and enhance their meaning. The study’s main aim is to identify how oxymoron elements are used in language and literature in Qahhor’s "Muhabbat" and to analyze their artistic and semantic roles. The results of the study show that Abdulla Qahhor, through his unique creative style, fully conveys complex internal feelings and contradictions to readers through oxymorons. Additionally, the article focuses on revealing the semantic and structural aspects of literary texts through the analysis of oxymorons.